An enhanced multiphase ISPH-based method for accurate modeling of oil spill. Issue 4 (1st October 2020) - Shimizu, Yuma; Khayyer, Abbas; Gotoh, Hitoshi; Nagashima, Ken
ABSTRACT: Accurate prediction of oil dispersion has been challenging due to its highly deformed/dispersed interface as well as small-scale oil-water mixing. In this paper, a refined Incompressible SPH (Smoothed Particle Hydrodynamics)-based method is proposed for simulations of oil spill problems. In the proposed method, the presence of oil is taken into consideration with concentration function and physical properties of computational points (particles), i.e. density and viscosity, are varied based on the concentration of oil. The proposed method incorporates a LES-based turbulence model, namely SPS (Sub-Particle-Scale) turbulence model, in order to capture small-scale turbulence effects. Diffusion equation is further implemented so as to reproduce the sub-particle-scale oil-water mixing effects. Interfacial surface tension is considered through potential-based modeling with consideration of the highly deformed/dispersed interface. A set of previously proposed refined schemes are also applied for accurate/robust simulations. The stability and accuracy of proposed ISPH-based method are investigated by conducting benchmark tests.